PENGARUH KEPEMIMPINAN SITUASIONAL DAN BUDAYA SEKOLAH TERHADAP PRODUKTIVITAS SEKOLAH PADA SMA - Rosmedi, Dudi; Chiar, M.; Syukri, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractHis study aims to determine the effect of (1) Principal Situational Leadership on School Productivity in Sub Rayon 2 High School Sambas Regency; (2) School Culture Against Productivity in Sub Rayon 2 High School Sambas Regency; (3) Principal Situational Leadership and School Culture Against Productivity in Sub Rayon 2 High School Sambas Regency. In this study using a quantitative research approach with descriptive analytical methods. The subjects of this study were teacher teachers in sub-rayon 2 high school in Sambas Regency with a total of 100 research subjects. The instrument used in the research is the Principal Situational Leadership instrument, School Culture instruments and School Productivity instruments using a Likert scale.The hypothesis testing conducted in this study uses multiple regression techniques. The results of the analysis show that: (1) there is the effect of the Principal Situational Leadership on School Productivity with a value of 4.8%; (2) there is an influence of School Culture on School Productivity with a value of 7.1%; and (3) there is the effect of Principal Situational Leadership and School Culture on School Productivity with a value of 14.36%.Keywords: Situational Leadership School School Productivity Culture